Memorandum of Understanding between the Journalism Training and Research Initiative, IGS, BRAC University and PROGATI on Granting (2011) - Journalism Training and Research Initiative, Institute for Governance Studies; PROGATI (Journalism Training and Research Initiative, IGS and PROGATI, 2013)
Mid-career journalists are typically not provided the funding or time to conduct in-depth investigations. They also are unlikely to have time to sharpen their research and investigation skills while working as reporters. The fellowship program will provide these journalists with time, funding and mentors that will enable them to strengthen their skills and gain valuable experience in investigating issues of importance to the general public. Through the focus on public audit reports, the fellowship program will introduce a rich source of data on corruption and mismanagement and generate demand for media use of audit data.